2007
DOI: 10.3758/cabn.7.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of scopolamine and lorazepam on working memory maintenance versus manipulation processes

Abstract: argued that, like neuropsychological studies of brain-damaged patients, which have played a critical role in advancing the understanding of normal and abnormal memory mechanisms, investigation of drug-induced amnesia can also be a powerful tool for elucidating memory mechanisms. In fact, investigation of drug-induced amnesia has several distinct advantages over traditional studies of amnesic patients. Most importantly, unlike the memory deficits found in amnesic patients, effects of drugs on memory processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
2
14
0
1
Order By: Relevance
“…The two working memory tasks are variants of the classic Sternberg task (Sternberg 1969) and were administered using procedures similar to those described by Mintzer and Griffiths (2007). During each experimental session, standardized instructions were read to the participants before each task (each block of the modified Sternberg manipulation task; see below), and practice trials were presented before the experimental trials to ensure that the participants understood and performed the tasks correctly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two working memory tasks are variants of the classic Sternberg task (Sternberg 1969) and were administered using procedures similar to those described by Mintzer and Griffiths (2007). During each experimental session, standardized instructions were read to the participants before each task (each block of the modified Sternberg manipulation task; see below), and practice trials were presented before the experimental trials to ensure that the participants understood and performed the tasks correctly.…”
Section: Methodsmentioning
confidence: 99%
“…The order of presentation of trials from the three conditions was random and the probed digit represented the correct position of the probed letter on half of the trials. Dependent measures included the accuracy of the response (i.e., yes or no) and reaction time from the onset of the probe to a participant’s response (see Mintzer and Griffiths 2007 for further detail).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some of the studies, most of which had small sample sizes, may have lacked the power to detect a potential medication effect. This is particularly relevant for the studies discussed above that examined PTSD patients who were taking benzodiazepines or antidepressants at the time of the study, because it has been clearly demonstrated that these drugs can affect memory performance 17,18 as well as emotional processing. 19 In addition to memory, psychomotor functioning and concentration are the cognitive domains most commonly affected by commonly used prescription medications.…”
Section: Effects Of Psychotropic Medications On Task Performance In Ptsdmentioning
confidence: 99%
“…Working memory refers to a brain system that provides temporary storage and manipulation of information, supporting human thought processes by providing an interface between perception, long-term memory and action [1][2][3] . Studies have suggested that working memory is mediated by the continuous activity of prefrontal cortex (PFC) neurons [4,5] , and the PFC plays an important role in working memory [6,7] .…”
Section: Introductionmentioning
confidence: 99%